PENYULUHAN NYERI PUNGGUNG PADA IBU HAMIL DI POSYANDU KEMUNING 512 KESATRIAN KOTA MALANG - M. Ardiansyah; Ali Multazam; Tri Dewi Fransiska (Jurnal Pemantik, 2023)
Pregnancy is a very valuable event in a woman's life. During pregnancy, women will experience many changes in their posture, physiological and anatomical changes that occur during pregnancy can cause a decrease in functional activity. Often women will feel pain in the back which is caused by an increase in abdominal volume. This counseling aims to increase knowledge of pregnant women and how to reduce back pain during pregnancy. This outreach activity was carried out on 16 – 31 October 2023. Located at Posyandu Kemuning 512, Kesatrian Village, Malang City. Participants in this activity were pregnant women in the second and third trimesters with a total of 10 participants. The outreach media uses leaflets. Data collection was carried out using pre-test and post-test questionnaires. The results show that there is an increase in knowledge and it can be concluded that the majority of pregnant women have a better understanding of the back pain they often experience.